Negotiating racialised identities : indigenous teacher education in Australia and Canada - Reid, Carol (Altona, Vic. : Common Ground Publishing, 2004)
Drawing on a comparative socio-historical overview of racialisation in the Australian and Canadian contexts and interviews with staff, students and administrators in the AREP and NORTEP, the author reveals how the tensions and contradictions of Indigenous teacher education can be productive.
Bibliography: p. 269-283.
Also available in an electronic version via the Internet at the publisher's home page: http://www.theLearner.com
Keywords: Teachers -- Training of -- Australia; Teachers -- Training of -- Canada; Indigenous peoples -- Education (Higher) -- Australia; Indigenous peoples -- Education (Higher) -- Canada; Aboriginal Australian teachers -- Training of; Race relations - Racial discrimination - Social; Education - Distance and remote; Education - Skills and curriculum; Education - Indigenous studies; Education - Skills and curriculum - Cultural awareness; Education - Secondary - Curriculum; Attitudes - Indigenous perspectives; Race relations - Racial discrimination - Education; Education - Primary - Curriculum; Education - Grants and finance; Education - Teachers - Teacher-student relationships; Indigenous peoples - North America; Education - Tertiary - Curriculum; Race relations - Representation - Education; Education - Teachers - Teachers aids; Education - Teachers - Teacher education; New South Wales (NSW); Canada